Ancient Human Skeleton (15th–19th Centuries) with Mastoid Osteoma, Discovered in Iași (Romania) - Vasilica-Monica Groza; Ozana-Maria Petraru; Mariana Popovici; Luminița Bejenaru (Memoirs of the Scientific Sections of the Romanian Academy, 2019)
This study is focused on a case of mastoid osteoma, a benign tumor reported in a skeletal sample found at the “Adormirea Maicii Domnului” Roman Catholic Cathedral of Iași (Romania). The sample, containing 89 skeletons (children, adolescents, adults, mature and senile) originates from inhumation tombs and reburials, dating from the 15th–19th centuries. Bone benign tumors (osteomas) can be dangerous, as they may grow and compress the healthy tissues. Osteomas, quite rare in the temporal bone, could be caused by trauma, chronic infection, hormonal disfunctions, etc. The osteoma described in this paper was identified in the cranium of a mature male, in the mastoid area of the left temporal bone. Macroscopical examination, radiography and computed tomography (3D) were used to assess the cranium; the results show a homogeneous bone mass identified as an osteoma, a bone tumor type reported for archaeological samples.